Involvement of a vascular hypersensitive response in quantitative resistance to Ralstonia solanacearum on tomato rootstock cultivar LS‐89. (11th May 2016) - Nakaho, K.; Seo, S.; Ookawa, K.; Inoue, Y.; Ando, S.; Kanayama, Y.; Miyashita, S.; Takahashi, H.
Abstract : Ralstonia solanacearum causes bacterial wilt disease in Solanaceae spp. Expression of the Phytophthora inhibitor protease 1 ( PIP1 ) gene, which encodes a papain‐like extracellular cysteine protease, is induced in R. solanacearum ‐inoculated stem tissues of quantitatively resistant tomato cultivar LS‐89, but not in susceptible cultivar Ponderosa. Phytophthora inhibitor protease 1 is closely related to Rcr3, which is required for the Cf‐2 ‐mediated hypersensitive response (HR) to the leaf mould fungus Cladosporium fulvum and manifestation of HR cell death. However, up‐regulation of PIP1 in R. solanacearum ‐inoculated LS‐89 stems was not accompanied by visible HR cell death. Nevertheless, upon electron microscopic examination of inoculated stem tissues of resistant cultivar LS‐89, several aggregated materials associated with HR cell death were observed in xylem parenchyma and pith cells surrounding xylem vessels. In addition, the accumulation of electron‐dense substances was observed within the xylem vessel lumen of inoculated stems. Moreover, when the leaves of LS‐89 or Ponderosa were infiltrated with 10 6  cells mL −1 R. solanacearum, cell death appeared in LS‐89 at 18 and 24 h after infiltration. The proliferation of bacteria in the infiltrated leaf tissues of LS‐89 was suppressed to approximately 10–30% of that in Ponderosa, and expression of the defence‐related gene PR‐2 and HR marker gene hsr203J was induced in the infiltrated tissues. These results indicated that the response of LS‐89 is a true HR, and induction of vascular HR in xylem parenchyma and pith cells surrounding xylem vessels seems to be associated with quantitative resistance of LS‐89 to R. solanacearum .